Ocena inwestycji na Warszawskiej Giełdzie Towarowej w okresie od stycznia 2002 roku do lipca 2004 roku - Drabik, Ewa; Górska, Anna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2004)
Nowadays the commodity exchange offers not only a wide range of operations such as trade in commodities but also future contracts and other types of financial transactions. While at the stock exchange one can encounter mainly shares, the commodity exchange epitomizes an impressive variety of negotiable units. Mutual funds and deposits, which are an alternative way of investing, also play a relevant role on the financial market. From economical point of view deposits are burdened with the smallest risk. According to the modem financial theory, the attitude towards a risk is considered as a very important aspect of the situation on the market. Not only behaviour of the investors but also political and economical events determine the situation on the market. The. behaviour of the investors is analysed by the cognitive psychology, which is associated with a new behavioural current in financial theory, which is called the behaviour finance. The aim of this paper is to check, if it is worth to invest at the commodity exchange. The analysis is carried out on the basis of the data from Warsaw Commodity Exchange in the span of3 years: 2002-2004.